Oldenburg Burnout Inventory - student version: cultural adaptation and validation into Portuguese - Campos,Juliana Alvares Duarte Bonini (2012)
The Oldenburg Burnout Inventory for college students (OLBI-S) was adapted to Brazilian Portuguese and its reliability and validity were measured in a sample of both Brazilian (n=958) and Portuguese (n=602) college students. The confirmatory factor analysis of the OLBI-S showed good fit but two items were removed since they lacked individual reliability (λ<.50). The new structure showed good fit to 2/3 of the test sample and was invariant to the other 1/3 of the total sample. Convergent validity and internal consistency were low, but discriminant, concurrent and divergent validity were good. The OLBI-S was not invariant in the Brazilian and Portuguese samples. The adapted OLBI-S did not show cross-cultural validity.